RELIGION STUDIES IN THE DIGITAL AGE: MAPPING THEORIES, METHODOLOGIES, AND APPROACHES IN DIGITAL RELIGION STUDIES - Aisyah, Lisfa Sentosa; Hidayatullah, Rahmat; Nisa, Muria Khusnun (ILMU USHULUDDIN, 2024)
This study aims to identify and explore trends in Digital Religion Studies, focusing on mapping the development of theories, methodologies, and approaches within this field. The research highlights the theoretical and methodological frameworks applied in analyzing the intersections of religion, media, and digital culture. Employing a qualitative approach through library research, this study adopts a Systematic Literature Review (SLR) method supplemented by thematic analysis. Based on a rigorous process of data identification and selection using inclusion and exclusion criteria, the study analyzed 41 journal articles and book chapters relevant to Digital Religion Studies. The findings reveal three key insights. First, the theoretical perspectives utilized in this field are predominantly influenced by media and communication theories, particularly those associated with the “Campbell Circle,” including theories of mediation, hypermediation, mediatization, deep mediatization, and the Religious-Social Shaping of Technology (RSST). Second, from a methodological perspective, qualitative approaches dominate the field, with limited engagement in quantitative methods. Most studies rely on secondary data from library research to build theoretical or conceptual arguments. Third, thematically, researchers tend to focus on central topics in Digital Religion Studies, such as rituals, communities, identity, and authority. The analysis underscores a predominance of studies addressing global or developed country contexts, with minimal exploration of local phenomena, particularly in Indonesia. This indicates that Digital Religion Studies has substantial potential for further development, especially in bridging the gap between global and local perspectives.